Effects of Long-Term Statin Therapy in Coronary Artery Disease Patients with or without Chronic Kidney Disease. (8th October 2015) - Huang, Huiling; Zeng, Chunmei; Ma, Yuedong; Chen, Yili; Chen, Cong; Liu, Chen; Dong, Yugang
Abstract : Introduction. The effect of long-term statin therapy is essential for secondary prevention of adverse clinical outcomes of coronary artery disease (CAD) patients. No study has compared the effects of long-term statin treatment in CAD patients with or without chronic kidney disease (CKD) and CKD only patients. Methods. We compared the effects of long-term statin therapy (average follow-up time 5.79 years) in terms of major adverse cardiovascular events (MACE), all-cause death, and cardiac death among 570 CAD patients with or without CKD and 147 CKD only patients. Results. The all-cause death and cardiac death of the patients with CAD and CKD (24.4% and 20.4%) doubled those of CAD only patients (10.7% and 9.1%) (P < 0.001 ). Long-term statin therapy dramatically reduced the rates of both MACE and all-cause death/cardiac death (by 20.5% and 28.6%/27.7%, resp.) in CAD and CKD patients. CKD only patients had no significant adverse clinical outcomes and were not responsive to long-term statin therapy. Conclusion. Chinese CAD patients with CKD had dramatically high rates of adverse clinical outcomes; for them, long-term statin therapies were exceptionally effective in improving morbidity and mortality. CKD patients who had no cardiovascular disease initially can prognose good clinical outcomes and do not require statin treatment.